The resolution game: A multiple selves perspective - Dimitri Migrow; Matthias Uhl (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The notion of choice inconsistency is widely spread in the literature on behavioral economics. Several approaches were used to account for the observation that people reverse their choices over time. This paper aims to explain the formation of resolutions regarded as internal self-binding devices. It moves away from anthropocentric neoclassicism and embraces a more atomistic notion of a player by defining intrapersonal agents as strategic actors. The magnitude of state-dependency is seen as a key driver of intrapersonal conflict modelled by the incongruity of the preferences of two opposing agents. The sequential conceptualisation basically allows for experimental testing
Keywords: C72; D01; 330; Multiple Selves; Agency; Intrapersonal Conflict; Resolutions; Self-Binding; Self-Control; Commitment; Entscheidung; Persönlichkeitspsychologie; Präferenztheorie; Selbstverpflichtung; Spieltheorie; Theorie